2020
DOI: 10.34067/kid.0000302019
|View full text |Cite
|
Sign up to set email alerts
|

Remote Treatment Monitoring on Hospitalization and Technique Failure Rates in Peritoneal Dialysis Patients

Abstract: Background An integrated kidney disease healthcare company implemented a peritoneal dialysis (PD) remote treatment monitoring (RTM) application in 2016. We assessed if RTM utilization associates with hospitalization and technique failure rates.Methods We used data from adult (age $18 years) patients on PD treated from October 2016 through May 2019 who registered online for the RTM. Patients were classified by RTM use during a 30-day baseline after registration. Groups were: nonusers (never entered data), moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 21 publications
0
47
0
Order By: Relevance
“…In a study of 49 patients on PD in Colombia, 118 remote monitoring led to improved pre‐emptive consultations, prescription adjustments and better blood pressure control. Another study from USA that evaluated telemedicine use in 6343 patients on PD, showed that hospital admission, hospital days and technique failure were 26% (IRR = 0.737; p = <.001), 32% (IRR = 0.680; p < .001) and 27% (HR = 0.726; p = .001) lower respectively in frequent users after 12 months versus non‐users 119 . While telemedicine offers several advantages, a few challenges in LLMICs must be recognized (Table 3), which should be addressed through optimal use of local resources.…”
Section: Telemedicine To Promote Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 49 patients on PD in Colombia, 118 remote monitoring led to improved pre‐emptive consultations, prescription adjustments and better blood pressure control. Another study from USA that evaluated telemedicine use in 6343 patients on PD, showed that hospital admission, hospital days and technique failure were 26% (IRR = 0.737; p = <.001), 32% (IRR = 0.680; p < .001) and 27% (HR = 0.726; p = .001) lower respectively in frequent users after 12 months versus non‐users 119 . While telemedicine offers several advantages, a few challenges in LLMICs must be recognized (Table 3), which should be addressed through optimal use of local resources.…”
Section: Telemedicine To Promote Pdmentioning
confidence: 99%
“…116 Also, a nationwide cohort study from Qatar has reported a higher but non- (HR = 0.726; p = .001) lower respectively in frequent users after 12 months versus non-users. 119 While telemedicine offers several advantages, a few challenges in LLMICs must be recognized (Table 3), which should be addressed through optimal use of local resources.…”
Section: Pd In Setting Of Covid-19 and Future Pandemicsmentioning
confidence: 99%
“…The present study joins others showing a beneficial impact of RPM on outcomes, such as hospitalization or resource consumption. 10,11,27 These RPM programs, supported by the new technological tool, can be a lever for improving PD therapy, analogously to the positive experiences of RPM that have been reported in other areas of medicine, such as cardiology and neurology, to name a few. 32 34…”
Section: Discussionmentioning
confidence: 86%
“…31 The present study joins others showing a beneficial impact of RPM on outcomes, such as hospitalization or resource consumption. 10,11,27 These RPM programs, supported by the new technological tool, can be a lever for improving PD therapy, analogously to the positive experiences of RPM that have been reported in other areas of medicine, such as cardiology and neurology, to name a few. [32][33][34] The strengths of this study include the relatively large number of patients that is greater than in previous reports and that we applied robust statistical matching techniques to deal with the problem of confounding that is inherent in observational studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation